Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pengguna Bus Di Kota Serang: Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pengguna Bus Di Kota Serang - IRWAN, IRWAN ZAINI; Handoko, Pryo (NIAGARA Scientific Journal, 2024)
This research was conducted to find out whether many people still use bus transportation services in the city of Serang, this is considering the rapid development of railway companies in Indonesia, including in the city of Serang. The aim of this research is to determine the influence service quality and price on consumer satisfaction of bus users in Serang City, as well as to determine the influence of service quality and price simultaneously on onsumer satisfaction of bus users in Serang City. This research uses quantitative methods with regression analysis techniques. The population of this research is bus users in the city of Serang. The research sample used random sampling statistics with a research sample of 55 Serang city bus user. Data collection was carried out by distributing questionnaires. Data was analyzed using the SPSS application. The research results show that service quality has a positive effect on consumer satisfaction and price has a positive effect on consumer satisfaction. The magnitude of the influence of the two independent variables on the dependent can be seen from the R Square value, is 73.6%, While the remainder is influenced by other variables at 26.4%.